CORRELATION OF INDIVIDUAL CHARACTERISTICS WITH WORK STRESS IN CALL CENTER AGENTS - Evi Maulani Rizki; Noeroel Widajati; Ayu Nurjanah (Universitas Pahlawan Tuanku Tambusai, 2023)
A call center job in the service industry requires providing the best client service possible. Call Center agents experience a variety of potential sources of stress in the course of performing their duties. This study tries to discover whether there is a connection between individual characteristics and workplace stress. This type of analytic observational study with a cross-sectional design with a population of 187 people with a sample of 45 people using simple random sampling at call center agents at PT. Infomedia Humanika Surabaya. Secondary data from company profiles and primary data from preliminary studies and questionnaires using the Depression Anxiety and Stress Scales instrument are utilized to collect the data. (DASS-42). Using the cross-tabulation analysis method, the de Vaus contingency coefficient is subsequently utilized to interpret the data. There is severe work stress of 51.1% for most workers, the relationship between gender and work stress is moderate (0.407), the relationship between age and work stress is moderate (0.588), the relationship between education level and low work stress (0.175), the relationship between marital status and low work stress (0.395). There is a moderate correlation between gender, age, and work stress, whereas the correlation between education level, marital status, and work stress is low.